Pertanggungjawaban Tentang Streamer Game Yang Mempromosikan Situs Slot Judi Online Saat Live Streaming Dalam Perspektif Hukum Pidana - Tegar Charisma, Christian Alam; Septianita, Hesti (Universitas Ekasakti, 2024)
This research was motivated by game streamers who promoted online gambling slot sites during live streaming regarding saweran acceptance. This is because technology is increasingly advanced, especially social media, which not only has positive impacts, but negative impacts as well. This research uses a normative juridical method which uses the main source of secondary data through reviewing library materials including primary, secondary and tertiary legal materials. The data obtained was analyzed descriptively qualitatively. From the results of the discussion it can be concluded that Indonesia has gambling criminal regulations, such as the old Criminal Code Articles 303 and Article 542 which were later passed by Law Number 7 of 1974 changing the punishment in Article 303 and changing the mention of Article 542 to 303 bis, as well as Government Regulation Number 9 1981 concerning the implementation of gambling control and in Article 426, Article 427 of the new Criminal Code which will come into effect in 2026. Online gambling is regulated in Law Number 11 of 2008 concerning Information and Electronic Transactions and its amendments. In terms of disseminating information, broadcast content is prohibited from containing gambling as stated in Article 27 of the ITE Law via internet-based electronic media. With the provisions, game streamers who are proven to be promoting online gambling and ordering their viewers to take part in gambling games in accordance with Article 55 of the Criminal Code can be held accountable with criminal sanctions in Article 45 paragraph (3) of the second amendment to the ITE Law with a heavier criminal threat than the previous provisions.